2019
DOI: 10.1002/jcb.28544
|View full text |Cite
|
Sign up to set email alerts
|

Mitigative effects of the bioactive flavonol fisetin on high‐fat/high‐sucrose induced nonalcoholic fatty liver disease in rats

Abstract: Background: Worldwide growing rates of obesity are correlated with the rising prevalence of nonalcoholic fatty liver disease (NAFLD) with limited available therapeutics. Aim: The present study was undertaken to investigate the modulatory effects of dietary supplementation fisetin on hepatocyte nuclear factor 4 α (HNF4α) gene expression, hepatic lipin-1 signaling, thioredoxin-interacting protein (TXNIP) levels, poly-(ADP-ribose)-polymerase-1 (PARP-1) activity, as well as some oxidative stress parameters in a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 62 publications
(113 reference statements)
0
13
0
Order By: Relevance
“…As aforementioned, fisetin is a flavonol compound that regulates lipid metabolism disorders, and anti-aging and anti-oxidation activities (30)(31)(32). A previous research has demonstrated that fisetin can inhibit the binding of ox-LDL to class B scavenger receptor cluster of differentiation 36 on macrophages and reduce foam cell formation to provide anti-AS effects (33).…”
Section: Discussionmentioning
confidence: 99%
“…As aforementioned, fisetin is a flavonol compound that regulates lipid metabolism disorders, and anti-aging and anti-oxidation activities (30)(31)(32). A previous research has demonstrated that fisetin can inhibit the binding of ox-LDL to class B scavenger receptor cluster of differentiation 36 on macrophages and reduce foam cell formation to provide anti-AS effects (33).…”
Section: Discussionmentioning
confidence: 99%
“…Based on those findings, we studied human liver samples, and demonstrated a strong positive correlation between mRNA levels for HNF4α and SHBG, and found an inverse relationship with the amount of liver triglyceride ( 19 ). It is now known that HNF4α expression is reduced in rodents fed a high fat diet ( 20 ), and in liver samples from human patients with NASH ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, fisetin protected aging-induced rat brain degeneration by suppressing oxidative stress, inflammation, and apoptosis (Singh et al, 2018). Recently, fisetin was shown to impart beneficial effects in non-alcoholic fatty liver disease in male albino rats by the suppression of oxidative stress (Gaballah, El-Horany, & Helal, 2019). In mice, hepatic inflammation stimulated by a high fat-diet was blocked by fisetin (Xu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%